Identification of polycyclic aromatic hydrocarbons and methoxylated phenols in wood smoke emitted during production of charcoal - Re-Poppi, N.; Santiago-Silva, M. R. (Vieweg, 2002)
More than 130 organic substances in dichloromethane-methanol (4: 1) extracts of particulate matter and the gaseous phase from wood burning for the production of charcoal have been identified by capillary gas chromatography coupled with low-resolution mass spectrometry (GC-MS), use of GC retention indices, and comparison with authentic standards. Many of the substances identified are methoxyphenols (derivatives of syringol and guaiacol), polycyclic aromatic hydrocarbons (PAH), oxidized PAH (oxy-PAH), and levoglucosan, the last being a monosoccharide derivative from the thermal breakdown of cellulose. The amount of unsubstituted PAH was greater than that of methyl- and dimethyl-substituted homologs.
Keywords: gas chromatography-mass spectrometry; polycyclic aromatic hydrocarbons; wood burning; charcoal; retention indices